If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8m + 9 = 6m + 19 Reorder the terms: 9 + 8m = 6m + 19 Reorder the terms: 9 + 8m = 19 + 6m Solving 9 + 8m = 19 + 6m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-6m' to each side of the equation. 9 + 8m + -6m = 19 + 6m + -6m Combine like terms: 8m + -6m = 2m 9 + 2m = 19 + 6m + -6m Combine like terms: 6m + -6m = 0 9 + 2m = 19 + 0 9 + 2m = 19 Add '-9' to each side of the equation. 9 + -9 + 2m = 19 + -9 Combine like terms: 9 + -9 = 0 0 + 2m = 19 + -9 2m = 19 + -9 Combine like terms: 19 + -9 = 10 2m = 10 Divide each side by '2'. m = 5 Simplifying m = 5
| -7/5y=-35 | | 7+1/7l=-2 | | -45=-9x+5 | | 26n+17=-42 | | 3n-1-5n=27 | | 192/-4*4*4 | | 2x+76=114 | | 4-1/2q=33-q | | -2x^2+9x-5=0 | | -7d=-42 | | 4-1/2=33-q | | 8n+6=34 | | -3x+10=13 | | 2/3a | | 2x+16=114 | | -3+10=13 | | 4.50x+8.25=1222.50 | | 3+4(7-9*9)= | | 4.50x+8.25=1222 | | 1+18/7n=-9 | | 8x^2+[-9x]+[10]+6x^2+[-6]+4= | | 4x^2=-289 | | -3/4+(-8)=7 | | 2(3x+4)=5x+30+12x | | -3/4(-8)=7 | | (2x^2+20x+18)/(x+9) | | -9+3x=-12 | | 3n/11=10 | | 3+4(7-9)= | | 8x+13x=17 | | 3+4(7-9)2= | | 28=-2m |